Dampak Peningkatan Kualitas Permukiman Kumuh Perdesaan terhadap Pengurangan Peluang Kejadian Bencana : Kasus Kebijakan Dana Desa di Indonesia - Simanjuntak, Ruth Agustina (Jurnal Kebijakan Ekonomi, 2022)
This study attempts to estimate the effect of rural slum upgrading on reducing the probability of flood and landslide disasters in the rural slum areas in Indonesia. By using a difference-in-differences (DID) approach with the logit regression model, this study analyzes the effect of the village funds in 24,343 villages in Indonesia within the period of 2006-2018. The results show that, after the implementation of the village fund policy in the rural slum areas, the probability of the occurrence of flood and landslide disasters in the treatment group, i.e. villages with high-density slums, is 0.761 times lower than the control group, i.e., villages with low-density slums, with 1% level of significance. These results show that the development and / or improvement of infrastructure’s quality, at the high-density rural slum areas, have effectively lessened the probability of the occurrence of disaster events.